Single‐Contact, Four‐Terminal Microelectromechanical Relay for Efficient Digital Logic - Reynolds, James D.; Rana, Sunil; Worsey, Elliott; Tang, Qi; Kulsreshath, Mukesh K.; Chong, Harold M. H.; Pamunuwa, Dinesh (Advanced electronic materials, 2023)
Nano and microelectromechanical relays can be used in lieu of transistors to build digital integrated circuits that can operate with zero leakage current at high operating temperatures and radiation levels. Four‐terminal (4‐T) relays facilitate efficient logic circuits with greatly reduced device counts compared to three‐terminal (3‐T) relay implementations. Existing 4‐T relays, however, require two moving contacts to simultaneously land on two stationary electrodes, which can adversely impact reliability, or have complex out‐of‐plane fabrication methods that can reduce yield and increase cost while having poor scalability. In this work an in‐plane four‐terminal relay with a single moving contact is demonstrated for the first time, through successful fabrication and characterization of prototypes with a critical dimension of 1.5 µm. Body biasing is shown to reduce the pull‐in voltage of this 4‐T relay compared to a 3‐T relay with the same architecture and footprint. The potential of the 4‐T relay to build efficient logic circuits is demonstrated by fabricating and characterizing a 1‐to‐2 demultiplexer (DEMUX) circuit using only two devices, a saving of eight devices over a 3‐T relay implementation. Nano and microelectromechanical relay‐based digital circuits offer the zero‐standby‐power and harsh‐environment capability required for IoT devices. The first in‐plane four‐terminal relay with a single contact to enable efficient and reliable circuits is reported here. Body biasing to reduce operating voltage and a 1‐to‐2 demultiplexer built using only two relays are demonstrated on prototypes with a critical dimension of 1.5 µm.